The Story of Suffragettes’ Campaign as Reflected in Suffragette: A Film Directed By Sarah Gavron (Feminist Literary Criticism) - Siti Lika; Dodi Oktariza; Asridayani Asridayani (Universitas Muara Bungo, 2018)
This research analyzes about the suffragettes’ story in campaigning women’s suffrage as reflected in Suffragette film. The purposes of this research are to explain bad treatments over women in male – dominated society, to describe the struggles of the suffragettes in suffragettes’ campaign pursuing the “votes for women” and the related history facts toward suffragettes’ campaign. In analyzing the research, the writer uses feminist literary criticism and some supporting theories. The method used in this research is descriptive qualitative. The data is formed in words and pictures. The data is analyzed through four procedures: identifying, classifying, analyzing and making conclusion. The results of this research are bad treatments over women in male – dominated society: women’s stereotyping, inequality in the workplace, and women’s subordination in marriage. Later, the writer finds out the struggle and the suffering of these women in campaigning women’s suffrage: consciousness – raising, peaceful campaign, and militant campaign; the last, the writer finds some related history facts toward suffragettes’ campaign as reflected in Suffragette film. Key words: Struggle, Suffering, Suffragette, Women’s suffrage campaign, Feminism, History